1994
DOI: 10.1111/j.1348-0421.1994.tb01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Type 1 Fimbriae of Salmonella typhi

Abstract: Type 1 fimbriae have been purified from a Salmonella typhi strain of clinical origin. Purified fimbriae retained their ability to bind to erythrocytes in a mannose-inhibitable fashion and, in doing so, behaved preferentially as a monovalent adhesin. SDS-PAGE analysis of the fimbrial preparation showed the presence of a 20-kDa major polypeptide component (fimbrillin) and of additional larger polypeptides present in smaller amounts. The amino-terminal sequence of fimbrillin was determined and turned out to be ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…For instance, the fim operon is well conserved among Salmonella serotypes, as indicated by Southern blot analysis (6,45). However, the fim operon in serotypes Typhimurium and Typhi encodes an adhesin, termed type 1 fimbriae, which mediates mannose-sensitive hemagglutination (18,31,36), whereas in serotype Gallinarum, it encodes surface appendages, termed type 2 fimbriae, which do not mediate mannose-sensitive hemagglutination (13,37). These differences in the binding specificity of the adhesin encoded by the fim operon are not detected by Southern hybridization (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the fim operon is well conserved among Salmonella serotypes, as indicated by Southern blot analysis (6,45). However, the fim operon in serotypes Typhimurium and Typhi encodes an adhesin, termed type 1 fimbriae, which mediates mannose-sensitive hemagglutination (18,31,36), whereas in serotype Gallinarum, it encodes surface appendages, termed type 2 fimbriae, which do not mediate mannose-sensitive hemagglutination (13,37). These differences in the binding specificity of the adhesin encoded by the fim operon are not detected by Southern hybridization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2). Evidence for expression of fimbriae assembled by the chaperone-usher-dependent pathway in serotype Typhi is so far only available for the fim operon (18,31). Thus, with the exception of fim, all operons described in this study should be considered putative.…”
Section: Vol 69 2001mentioning
confidence: 99%
“…The type 1 fimbriae of the genus Salmonella are composed primarily of FimA protein subunits (9,12). However, for direct binding to oligomannosidic structures, another protein, called FimH adhesin and located at the distal end of the fimbrial shaft, is responsible (7,10,17).…”
mentioning
confidence: 99%
“…A comparison of amino acid sequences of active FimH adhesins from S. enterica serovar Typhimurium (17), Salmonella enterica serovar Typhi (12), and S. enterica serovar Enteritidis (unpublished data) revealed that both inactive adhesins from biovar Gallinarum and biovar Pullorum are characterized by the presence of iso- FimH adhesins in all other analyzed Salmonella serovars, and it is the only consistent amino acid substitution differentiating active and inactive proteins. This finding raised the possibility that the T78I mutation could be responsible for the loss of their binding properties.…”
mentioning
confidence: 99%
“…Fimbriae from salmonellae have been puri®ed and characterised before [5,20,23] but, to the authors' knowledge, the potential of SEF 21 to compartmentalise and survive passage through the gastrointestinal tract has not been investigated. Indeed, few studies have dealt with the interactions of isolated ®mbriae or pili with the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%